Psychosocial constraints experienced by caregivers of children with special needs in Kelantan, Malaysia/ Siti Nor Ismalina Isa ... [et al.] - Isa, Siti Nor Ismalina; Ishak, Ismarulyusda; Ab Rahman, Azriani; Mohd Saat, Nur Zakiah; Che Din, Normah; Lubis, Syarif Husin; Mohd Ismail, Muhammad Faiz; Mohd Suradi, Nur Riza (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Families of children with special needs (CWSN) experience many difficulties and are socioeconomically disadvantaged when compared to families of typical children. The burden of care, social, financial and other stressful situations are considered to be crucial in determining the quality of life (QoL) of the families of CWSN. The purpose of this study was to explore the psychosocial constraints faced by caregivers of CWSN in Kelantan, Malaysia which affected their QoL. A qualitative study was conducted utilizing the phenomenology approach. A total of 22 participants were recruited for face-to-face, in-depth interviews. The sample was comprised of caregivers (n = 14), community-based rehabilitation trainers (n = 4), special education teachers (n = 3), and welfare officer (n = 1). Each interview was recorded on audio-tape. The recordings were transcribed and thematic content analysis was used to create codes and identify emerging themes. It was found that psychosocial constraints experienced by the caregivers were associated with common themes such as psychological factors, accessibility to services, socio cultural issues, social supports, and system and policy. Thus, intervention strategies to improve the QoL of caregivers of CWSN should target the family unit and consider the psychosocial factors of the caregivers.